1997
DOI: 10.1111/j.1525-1470.1997.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Xp Microdeletion Syndrome Characterized by Pathognomonic Linear Skin Defects on the Head and Neck

Abstract: We describe a new case of a rare syndrome characterized by ocular abnormalities and pathognomonic linear skin defects. This syndrome is the result of an unbalanced translocation resulting in a deletion of the distal end of the short arm of the X chromosome. We report the thirteenth case and review the clinical and cytogenetic aspects of this disorder. In addition we discuss new findings pertaining to the histopathology of the skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
5
21
0
Order By: Relevance
“…Occasional abnormalities include agenesis of the corpus callosum, sclerocornea, chorioretinal abnormalities, infantile seizures, congenital heart defect, and mental retardation. At least 30 patients have been described so far (Friedman et al, 1988;Al-Gazali et al, 1990;Donnenfeld et al, 1990;Temple et al, 1990;Allanson and Richter, 1991;Gericke et al, 1991;Thies et al, 1991;Lindor et al, 1992;Naritomi et al, 1992;Happle et al, 1993;Bird et al, 1994;Eng et al, 1994;Lindsay et al, 1994;McLeod et al, 1994;Mücke et al, 1995;Camacho et al, 1997;Paulger et al, 1997;Cox et al, 1998;Ogata et al, 1998;Stratton et al, 1998;Zvulunov et al, 1998;Kono et al, 1999;Kayserili et al, 2001;Anguiano et al, 2003).…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasional abnormalities include agenesis of the corpus callosum, sclerocornea, chorioretinal abnormalities, infantile seizures, congenital heart defect, and mental retardation. At least 30 patients have been described so far (Friedman et al, 1988;Al-Gazali et al, 1990;Donnenfeld et al, 1990;Temple et al, 1990;Allanson and Richter, 1991;Gericke et al, 1991;Thies et al, 1991;Lindor et al, 1992;Naritomi et al, 1992;Happle et al, 1993;Bird et al, 1994;Eng et al, 1994;Lindsay et al, 1994;McLeod et al, 1994;Mücke et al, 1995;Camacho et al, 1997;Paulger et al, 1997;Cox et al, 1998;Ogata et al, 1998;Stratton et al, 1998;Zvulunov et al, 1998;Kono et al, 1999;Kayserili et al, 2001;Anguiano et al, 2003).…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…Remarkably, four female patients with an apparently normal karyotype have also been described (Happle et al, 1993;Bird et al, 1994;Cox et al, 1998;Zvulunov et al, 1998) suggesting that submicroscopic rearrangements or "short length" mutations in a yet unidentified gene may also be responsible for the trait. To date, three affected males and twin brothers have been reported, all with an XX complement and a translocation between Xp and Yp (Lindsay et al, 1994;Paulger et al, 1997;Stratton et al, 1998;Kono et al, 1999;Anguiano et al, 2003). A sixth patient had ambiguous genitalia and a 46,XX karyotype (Camacho et al, 1997).…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…Zvulunov et al [1998] described peculiar ultrastructural ®ndings (cytoplasmic bodies within keratocytes). Recent studies have reported smooth muscle hamartomata, rather than the presumed dermal aplasia [Paulger et al, 1997;Stratton et al, 1998]. Hypoplasia or agenesis of the corpus callosum is frequently reported in the syndrome [for reviews of reported cases, see Bird et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…A few individuals had developmental delay, short stature and facial dysmorphism (Table 1). Rarely, hearing loss and anal atresia with ectopic anus and fistula, as seen in patient 5 have also been observed in other cases [13,35,40,41]. Patient 2 and one reported girl [4] carried the HCCS nonsense mutation c.589C > T (p.R197*).…”
Section: Discussionmentioning
confidence: 58%